2021
DOI: 10.1172/jci151800
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the GLP-1 receptor agonist dulaglutide in primary polydipsia

Abstract: Background Primary polydipsia, characterized by excessive fluid intake, carries the risk of water intoxication and hyponatremia, but treatment options are scarce. Glucagon-like peptide-1 (GLP-1) reduces appetite and food intake. In experimental models, they also play a role in thirst and drinking behavior. The aim of this trial was to investigate whether GLP-1 receptor agonists reduce fluid intake in patients with primary polydipsia. MethodsIn this randomized, double-blind, placebo-controlled, 3-week crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Primary polydipsia has traditionally been linked to psychiatric disease, such as schizophrenia spectrum disorder ( 125 ), but is increasingly reported in healthy people without psychiatric comorbidities ( 40 , 126 , 127 ), as it was the case for our patient. In clinical practice, cognitive behavioral therapy is used to treat primary polydipsia and was successful in our patient.…”
Section: Back To Patient Presentationmentioning
confidence: 62%
See 1 more Smart Citation
“…Primary polydipsia has traditionally been linked to psychiatric disease, such as schizophrenia spectrum disorder ( 125 ), but is increasingly reported in healthy people without psychiatric comorbidities ( 40 , 126 , 127 ), as it was the case for our patient. In clinical practice, cognitive behavioral therapy is used to treat primary polydipsia and was successful in our patient.…”
Section: Back To Patient Presentationmentioning
confidence: 62%
“…However, guidelines for the management of this syndrome are lacking and medical treatment options are scarce ( 128 ). We have recently shown that a 3-week treatment with the glucacon-like peptide-1 receptor agonist dulaglutide reduces thirst, daily fluid intake, and 24-hour urine output in primary polydipsia ( 126 ). This proof of concept study provides a novel therapeutic approach and the GLP-1 receptor agonist may in the future become an interesting treatment option for these patients.…”
Section: Back To Patient Presentationmentioning
confidence: 99%
“…This study combined data from two prospective studies conducted at the University Hospital Basel, Switzerland. The methodology of both studies was similar with the aim to elucidate the effect of GLP-1 receptor agonists on drinking behavior in 34 patients with primary polydipsia [14] and in 20 healthy volunteers [15] in a randomized placebo-controlled crossover design. For the present exploratory analysis, only data of participants during the placebo phase were evaluated.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…For the present exploratory analysis, only data of participants during the placebo phase were evaluated. Full details of the studies' rationale, design, and statistical analysis have been published elsewhere [14,15]. Inclusion criteria for patients with primary polydipsia were age ≥ 18 years, polyuria of > 50 ml/kg/day, and polydipsia of > 3000 ml/day.…”
mentioning
confidence: 99%
“…On the other hand, in addition to the brain effects described above, GLP-1R agonists could also act on intestinal hyperpermeability and gut microbiota diversity, probably in a way that protects against the harmful effects of chronic drug use. Dulaglutide might thus be of extra interest as a clinical study with dulaglutide reporting a low number of aversive effects (Winzeler et al, 2021 ). Finally, GLP-1 also increases anti-inflammatory cytokines, providing another beneficial effect relevant for certain types of addictions.…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%